2014
DOI: 10.1186/1477-7819-12-26
|View full text |Cite
|
Sign up to set email alerts
|

The role of 18F-fluorodeoxyglucose positron emission tomography/computed tomography in the primary staging of rectal cancer

Abstract: BackgroundIn this study we aimed to determine the need for 18F-flourodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in the preoperative staging of rectal carcinoma in our large patient group according to level and location of tumor.MethodTotally, 97 patients diagnosed with primary rectal adenocarcinoma between May 2009 and July 2011 were included in the study. Preoperative staging was performed by evaluating contrast-enhanced thoracic, abdominal, and pelvic computed tomographies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…We assumed that ceCT could provide information about the enlargement of regional LNs; however, they have limited value during the evaluation of regional LN involvement because a normal-sized LN may have a tumor, and an enlarged LN may be reactive [21] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that ceCT could provide information about the enlargement of regional LNs; however, they have limited value during the evaluation of regional LN involvement because a normal-sized LN may have a tumor, and an enlarged LN may be reactive [21] .…”
Section: Discussionmentioning
confidence: 99%
“…LNs with increased F-18-FDG accumulation relative to surrounding soft tissues were considered metastatic, independent of their sizes. On ceCT imaging, a metastatic LN was defined as a lesion with short-axis diameter above 10 mm [21] . When there was a discrepancy between the interpreters' judge, a consensus was reached by discussion.…”
Section: F-18-fdg-pet/ct Image and Cect Interpretationmentioning
confidence: 99%
“…Studies have reported a wide range of CRC tumors detection 20 to 90%. There are many factors that contribute in this discrepancy, such as using of different screening protocols, gold standards, variable inclusion criteria, different time gap between the imaging tools, and the variability between the images readers [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…(22) This resulted in changes in treatment strategy or operation performed. Although PET-CT may not be sufficient in identifying N stage for rectal cancer, the utility of routine PET-CT for overall staging deserves further study.…”
Section: -F-fluorodeoxyglucose Positron Emission Tomography/computementioning
confidence: 98%